Mitochondrial Defunctionalization Supresses Tim-3-Galectin-9 Secretory Pathway in Human Colorectal Cancer Cells and Thus Can Possibly Affect Tumor Immune Escape - Sakhnevych, Svetlana S.; Yasinska, Inna M.; Fasler-Kan, Elizaveta; Sumbayev, Vadim V. (Frontiers in Pharmacology, 2019)
The Tim-3-galectin-9 secretory pathway is known to protect various types of cancer cells against host immune surveillance. We found that pharmacologically induced mitochondrial dysfunction leads to a reduced galectin-9 expression/exocytosis in human colorectal cancer cells and re-distribution of this protein (the effect described for various cellular proteins) into mitochondria.